ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BAYI BERAT LAHIR RENDAH DENGAN MODEL REGRESI LOGISTIK BINER MENGGUNAKAN METODE BAYES (Studi Kasus di Rumah Sakit Umum Daerah Kota Semarang) - Laily Nadhifah; Hasbi Yasin; Sugito Sugito (Jurnal Gaussian, 2012)
This study aims to elucidate several factors which affect low-birth-weight (LBW) infants in Semarang General Hospital (RSUD) in the period from July to December 2011. With regard to the MilleniumDevelopment Goals’s targets, which are predominantly intended to reduce the child mortality rate, serious investigations are highly needed to identify the factors that determine the rate of babies born with the low-birth-weight category. This problem can be solved with the Binary Logistic Regression model,using the Bayesian method. The Bayesian method is one of the parameter estimation technique which employ prior value as initial knowledge. The conducted research is to argue that both factors of age and the maternal hemoglobin level considerably give influence on LBW birth. Based on the research analysis, it is extremely recommended that mother to be pays much attention not to be pregnant at relatively young age and maintain the secure level of hemoglobin during pregnancy.